Six main innovation issues: a case of service innovation of postal and courier services in Malaysia - Noordin, Alminnourliza; Hasnan, Norlena; Osman, Nor Hasni (Universiti Tun Hussein Onn Malaysia, 2014)
Malaysia, together with Thailand, Indonesia and Philippines are looking forward to be a fully industrialized country by the year 2020. The Ministry of Science Technology and Innovation (MOSTI,2010) reported that Malaysia was ranked at 24th in the Innovation Competitiveness and also ranked at 26th in the Global Competitiveness Index for the year 2010-2011.As our nation could gain a huge profit from innovation activities, however, it will also come with risk. Therefore, several issues will encounter while engaging in innovation plan. This paper discusses innovation issues particularly in Malaysia. Specifically, this paper discusses six factors that have been identified to be main innovation issues and deliberates on the service innovation of postal and courier in Malaysia.